PENGARUH KEPEMIMPINAN TRILOGI, KEPUASAAN KERJA DAN KOMITMEN ORGANISASI TERHADAP PRODUKTIVITAS SDM (STUDI: KOPERASI DAN UMKM KUD KARYA MUKTI PROVINSI JAMBI) - Triyani Triyani (JURNAL ILMIAH EDUNOMIKA, 2021)
The purpose of this study was to describe (1) the influence of trilogy leadership on human resource productivity, (2) the effect of satisfaction on human resource productivity, (3) the effect of organizational commitment on human resource productivity. This research is a quantitative research, descriptive analysis method and method of analysis of the coefficient of determinants. The population is employees of KUD Karya Mukti Cooperative and UMKM Jambi Province, the sample technique is stratified random and sampling. The method used was questionnaire data, while the data analysis technique used simultaneous, partial, and linear regression data. The results of this study use a significant result of 0.005 indicating that there is a negative influence on trilogy leadership with the variable of human resource productivity. In addition, there is also an effect of job satisfaction on the productivity of human resources which has a negative and insignificant effect. Then there is organizational commitment that has a positive and significant effect on human resource productivity. Keywords: trilogy leadership, job satisfaction, organizational commitment, human resource productivity